Testing Monotonicity of Dosage-Effect Relationship by Mosteller’s Test and its Sequential Modification - Lienert, G. A.; Sarris, V. (Methods of Information in Medicine, 1968)
Mosteller’stest for predicted order is modified so that it can be applied as a sequential trend test: By sequential sampling of individuals showing some order of scores on a continuously distributed variable, the null hypothesis that a predicted order occurs by chance may be accepted or rejected in favor of the alternative hypothesis that it occurs in a numerically defined higher proportion as a result of the imposed experimental conditions.